Pilates and conditioning for athletes an integrated approach to performance and recovery - Lademann, Amy 1972-; Lademann, Rick 1974- (Human Kinetics, 2019)
Pilates and Conditioning for Athletes is a science-based, multi-discipline approach to athletic conditioning. It helps you build a strong and flexible foundation by infusing Pilates into complete training programmes. The text features proven assessment protocols that have helped elite athletes reach and stay at the pinnacle of their careers. These can be used to evaluate your movement patterns, ranges of motion, strength bases, flexibility and core strength. This comprehensive guide includes detailed instructions for over 124 Pilates mat and traditional conditioning exercises. These help you strengthen your core, improve your posture and increase your flexibility. It also features other tips such as breathing exercises and resistance training for strength and power. Pilates and Conditioning for Athletes also includes 19 foundational, intermediate and sport-specific workouts to help you achieve your performance goals. Whether you're a weekend warrior or a professional athlete you'll learn how to become stronger, faster and healthier with Pilates